Retinopathy of Prematurity and Blood Transfusion Protocols - P Mohagheghi; N Khosravi; H Samaii (Tehran University of Medical Sciences, 2003)
To determine the role of blood transfusion protocols on retinopathy of prematurity (ROP), a prospective cohort study on 57 premature infants under 1501 grams birth weight was performed. Fourteen day-old infants were divided into two groups randomly. Infants in group 1 (n=27) received packed red blood cell transfusion only if specific medical signs were met and their hematocrit level was under 30%. Infants in group 2 (n=30) received blood transfusion to maintain their hematocrit level > 40% regardless of their signs. All infants had an eye examination by indirect ophthalmoscopy from 28 to 40 days of life for detecting ROP. We did not find any significant difference in ROP incidence between both groups.